Integrative Impact of Corporate Governance and International Standards for Accounting (IAS, IFRS) in Reducing Information Asymmetry - Ahmed, Dler M.; Azhar, Z.; Mohammad, Aram J. (Polytechnic Journal of Humanities and Social Sciences, 2024)
Information asymmetry has become the foremost element that affects organizational performance, and this aspect demands the researchers’ emphasis. Thus, the present study examines the impact of corporate governance and the application of IAS standards on the information asymmetry in the oil industry in the Kurdish region. The study also investigates the mediating role of the application of IAS among corporate governance and information asymmetry in the oil industry in the Kurdish region. The researchers examine the comprehensive literature to investigate the association between understudy variables. The researcher concludes, on the basis of comprehensive literature, that the corporate governance and application of IAS standards have a positive association with information asymmetry in the oil industry in the Kurdish region. The researchers also conclude that the application of IAS significantly mediates among corporate governance and information asymmetry in the oil industry in the Kurdish region. The study guides the regulators in developing regulations related to reduce the information asymmetry using corporate governance and application of IAS standards. Keywords: Corporate governance, application of international standards for accounting, information asymmetry, Kurdish region.